Persepsi Siswa tentang Kompetensi Profesional Guru Bimbingan dan Konseling - Silvia Silvia Rosa; Marjohan Marjohan; Azrul Said (Universitas Negeri Padang, 2016)
This research is classified as  descriptive quantitative research. The research sample are 80 students SMPN7 of Padang. The findings this research: students' perceptions about the professional competence of teachers in terms of guidance and counseling master the concepts and practical assessment to understand the student's conditions, needs, and problems are in either category.